Utilization of Phenol as Carbon Source by the Thermoacidophilic Archaeon Saccharolobus solfataricus P2 Is Limited by Oxygen Supply and the Cellular Stress Response - Wolf, Jacqueline; Koblitz, Julia; Albersmeier, Andreas; Kalinowski, Jörn; Siebers, Bettina; Schomburg, Dietmar; Neumann-Schaal, Meina (Frontiers in Microbiology, 2021)
Present in many industrial effluents and as common degradation product of organic matter, phenol is a widespread compound which may cause serious environmental problems, due to its toxicity to animals and humans. Degradation of phenol from the environment by mesophilic bacteria has been studied extensively over the past decades, but only little is known about phenol biodegradation at high temperatures or low pH. In this work we studied phenol degradation in the thermoacidophilic archaeon Saccharolobus solfataricus P2 (basonym: Sulfolobus solfataricus) under extreme conditions (80 °C, pH: 3.5). We combined metabolomics and transcriptomics together with metabolic modelling to elucidate the organism’s response to growth with phenol as sole carbon source. Although S. solfataricus is able to utilize phenol for biomass production, the carbon source induces profound stress reactions, including genome rearrangement as well as a strong intracellular accumulation of polyamines. Furthermore, computational modelling revealed a 40 % higher oxygen demand for substrate oxidation, compared to growth on glucose. However, only 16.5 % of oxygen is used for oxidation of phenol to catechol, resulting in a less efficient integration of carbon into the biomass. Finally, our data underlines the importance of the phenol meta-degradation pathway in S. solfataricus and enables us to predict enzyme candidates involved in the degradation processes downstream of 2 hydroxymucconic acid.